The Problem of Meaning of Neurotic Anxiety in Psychology and Psychiatry - M Yu Norina; M S Pavlova (Peoples' Friendship University of Russia (RUDN University), 2011)
The article states the problem of the necessity of consideration of the neurotic anxiety meaning as there are few researches of anxiety meanings and the influence of value sphere on the expressiveness of the anxiety manifestations under neurotic disorders in modern science. The analysis and awareness of the subjective reasons and meanings of anxiety leads to a deeper and more constructive living through anxiety in the therapy process.